Superdiffusive Searching Skill in Animal Foraging - Dutta, Kishore (Discontinuity, Nonlinearity, and Complexity, 2026)
Random walk related to diffusion driven transport is widely used to describe phenomena in the context of physics, biology, statistics, and econometrics. However, contrary to the normal (Gaussian) diffusion process, anomalous diffusion takes place in many natural phenomena ranging from turbulence to animal foraging. In situations where spreading process is more rapid than the normal diffusion, the distribution of steps comprises many short movements broken episodically by less frequent long excursions, commonly known as Lévy flight. Recent quantification of high resolution foraging data of many free-ranging animals suggest that they display Lévy flight behavior in environments where prey is scarce. This article describes the fundamental properties of Lévy flight and how it encodes the statistical characteristics of the animal foraging patterns.